2019
DOI: 10.15655/mw/2019/v10i2/49642
|View full text |Cite
|
Sign up to set email alerts
|

Digital and Interactive Social Media among Middle East Women: Empirical TAM Study

Abstract: This study investigates the use of interactive media (WhatsApp) by Bahraini women to understand their decisions on how, why and when they use it. It supports the use of mobile technology applications to expand efficient communication and information among Arab women. Mobile technologies are very accessible to Arab women these days. A sample of 1,137 responses was collected, using a snowball sampling approach. Based on TAM literature, the study found that interactive media (e.g., WhatsApp) has enabled Bahraini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This category includes messages about mood or feelings, personal news that have significantly affected the individual, or the search for emotional support. It had already been pointed out in relation to WeChat [22] and WhatsApp [61], and even in relation to the use of SMSs among Saudi students, applications that in the past shared many of the characteristics obtained now with MIMs [11]. The interviews with…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This category includes messages about mood or feelings, personal news that have significantly affected the individual, or the search for emotional support. It had already been pointed out in relation to WeChat [22] and WhatsApp [61], and even in relation to the use of SMSs among Saudi students, applications that in the past shared many of the characteristics obtained now with MIMs [11]. The interviews with…”
Section: Discussionmentioning
confidence: 92%
“…This category includes messages about mood or feelings, personal news that has significantly affected the individual, or the search for emotional support. It had already been pointed out in relation to WeChat [22] and WhatsApp [61], and even in relation to the use of SMSs among Saudi students, applications that in the past shared many of the characteristics obtained now with MIMs [11]. The interviews with WeChat users showed that one type of interaction in this application was sympathetic companionship, defined by the author as a form of communication in which people seek psychological or emotional support from others [22], a category that is the same as the personal affective information in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of daily use of MIMs tends to be lower than for SNSs. The average of use fluctuates between 30 min/day and 2 h/day for WeChat (Zong et al , 2019; Lien and Cao, 2014), and it is around 55 min/day for WhatsApp (Kaye and Quinn, 2020; Elareshi and Ziani, 2019). LINE is once again the exception due to its low level of use, since 40% of its users use this application for a maximum of 30 min/day (Chou and Liu, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, during uprisings in Egypt, Libya, Tunisia, and Yemen, Arab women actively participated and remained prominent. Their contribution was also motivated by a long-term absence of women in Arab political scenarios and certain socio-political inequalities (AlSalem, 2016;Elareshi & Ziani, 2019). They took part in protests along with men to raise voices against discrimination, despotism, and absolutism.…”
Section: Bahrain General Elections 2018mentioning
confidence: 99%
“…In political communication, success in election campaigns depends on how candidates use their skills and abilities to master political communication, including political public relations with their voters and supporters using both new and old media platforms. However, such exercise might be not fully found in many Arab countries as in the western world, although social media is highly preferred in the Arab region (Elareshi & Ziani, 2019). It could be due to the lack of Arab professional campaign skills in using digital media (Ahmed et al, 2016;Calderaro, 2018;Karlsen & Enjolras, 2016), and how to apply such platform in online political communication that is also emphasised by McGregor and Mourao (2016).…”
Section: Theme 3: Self-presentationmentioning
confidence: 99%